1993
DOI: 10.1079/bjn19930054
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise on the riboflavin status of adult men

Abstract: Six sedentary to moderately active men with biochemical signs of riboflavin deficiency were studied under metabolic ward conditions to examine the effects of physical activity on riboflavin status. All participants were subjected to additional exercise (EXER) for an 18 d period between two maintenance (M1 and M2) periods (16 and 13 d respectively) of habitual physical activity. Energy balance and riboflavin intake were maintained throughout the study. Riboflavin status, as judged by a significant reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…Two subsequent studies by the same group 70,71 seemed to support the finding. In a more recent study, Soares et al 72 examined riboflavin status in male subjects with initially marginal E-GRAC results. Because of worsened indicators of riboflavin status during an 18-day exercise-period, the authors suggested increased riboflavin needs because of increased physical activity.…”
Section: Vitamins Of the B-complex Groupmentioning
confidence: 99%
“…Two subsequent studies by the same group 70,71 seemed to support the finding. In a more recent study, Soares et al 72 examined riboflavin status in male subjects with initially marginal E-GRAC results. Because of worsened indicators of riboflavin status during an 18-day exercise-period, the authors suggested increased riboflavin needs because of increased physical activity.…”
Section: Vitamins Of the B-complex Groupmentioning
confidence: 99%
“…In the present study, Zinc, Iron, Copper and Magnesium showed significant improvement after twelve weeks of yoga practices in experimental group while wait-list control group did not show any significant improvement. Earlier studies also reported that physical activity and yoga have led to improvement in micronutrient absorption24,25,26 ) . Improvement in Zinc, Iron, Copper, and Magnesium in experimental group can be attributed to twelve weeks of yoga training.…”
Section: Discussionmentioning
confidence: 91%
“…Due to practical constraints, including some mothers' unwillingness to allow blood sampling, biochemical investigations could not be done on all the mothers and children. Biochemical assessment of riboflavin status was included, since it is influenced by physical work (Belko et al, 1985;Soares et al, 1993). Haemoglobin was estimated by the cyanmethemoglobin method and riboflavin status by the erythrocyte glutathione reductase activation test (EGR-AC) (Bamji, 1981;Bayoumi and Rosalki, 1976).…”
Section: Methodsmentioning
confidence: 99%